Determinan Kesiapan Mahasiswa Pendidikan Akuntansi untuk Berkarir di Luar Profesi Guru (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the determinants of students' readiness for accounting education for careers outside the teaching profession which include self-efficacy, family support, entrepreneurship education, future orientation and work motivation. The population in this study were all students of Accounting Education class 2014 Faculty of Economics, State University of Semarang, amounting to 164 students and using a saturated sample. Collecting data using a questionnaire. Data were analyzed by descriptive analysis and multiple linear regression. The results showed that the work readiness of Accounting Education students for a career outside the teaching profession was in the ready category. Simultaneously, the percentage of the contribution of the influence of self-efficacy, family support, entrepreneurial education, future orientation and work motivation on the work readiness of Accounting Education students of 2014 is 45.2%. Partially, self-efficacy affects work readiness (17.81%), family support affects work readiness (0.45%), entrepreneurship education affects work readiness (0.01%), future orientation affects work readiness (5 ,24%) and work motivation has an effect on work readiness (2,59%).